Espalhamento de Férmions sob Influencia da Violação de Lorentz no Setor Fotônico - Santos, Frederico Elias Passos dos (2010)
The standard model extension is a theoretical framework which includes the possibility of Lorentz symmetry violation in the Standard Model of elementary interactions. In electrodynamics, this possibility is represented by the term, Kμν∝βFμνF∝β , that violates Lorentz symmetry without jeopardizing CPT symmetry, and the term ε∝μβνV∝Aμ∂βAν, which violates Lorentz and CPT symmetries. These additional terms are inserted in the Maxwell Lagrangena and alter the field equations, as well. In this work we study the influence of Lorentz violation in the photonic sector on fermion scattering processes, regarding individually the CPT-odd and CPT-even coefficients. At first, we present a review through some topics of great interest, as the Dirac equation, Dirac propagator, scattering matrix, Feynman rules, Casimir trick, and the evaluation of the differential cross sections. Next, we implemented the developed techniques to carry out the corrections (to the cross sections) induced by the Lorentz-violating terms. Our results reveal as each Lorentz-violating component changes the cross section. In the CPT-even case, we observed that the contribution of the term tr to the process e− + μ− → e− + μ− is of difficult detection once it can be disguised between the radioactive corrections. The contributions coming from the vector i imply an angular dependence in the differential cross section of the process e− + μ− → e− + μ−, and do not contribute for the process e− + e+ → μ− + μ+. The CPT-even coefficients, (Ke−)ij , lead to significant contributions in both cases. We highlight its influence in the pair electron-positron annihilation process, where they act as the only components that imply sensitive contributions. The contribution stemming from the CPT-odd sector, represented by the Carroll-Field-Jackiw term, is of less relevance, since the contribute are second order ones. Although we have initially developed a perturbative procedure for evaluating the cross section correction, it was also possible to evaluate the exact propagators of the CPT-odd and CPT-even sectors in a tensor closed form. Such tensor expressions may be used to rederive the cross section corrections.